Hydrogels with programmed spatiotemporal mechanical cues for stem cell-assisted bone regeneration - Bin Xue; Zhengyu Xu; Lan Li; Kaiqiang Guo; Jing Mi; Haipeng Wu; Yiran Li; Chunmei Xie; Jing Jin; Juan Xu; Chunping Jiang; Xiaosong Gu; et al. (Nature Communications)
Abstract Hydrogels are extensively utilized in stem cell-based tissue regeneration, providing a supportive environment that facilitates cell survival, differentiation, and integration with surrounding tissues. However, designing hydrogels for regenerating hard tissues like bone presents significant challenges. Here, we introduce macroporous hydrogels with spatiotemporally programmed mechanical properties for stem cell-driven bone regeneration. Using liquid-liquid phase separation and interfacial supramolecular self-assembly of protein fibres, the macroporous structure of hydrogels provide ample space to prevent contact inhibition during proliferation. The rigid protein fibre-coated pore shell provides sustained mechanical cues for guiding osteodifferentiation and protecting against mechanical loads. Temporally, the hydrogel exhibits tunable degradation rates that can synchronize with new tissue deposition to some extent. By integrating localized mechanical heterogeneity, macroporous structures, surface chemistry, and regenerative degradability, we demonstrate the efficacy of these stem cell-encapsulated hydrogels in rabbit and porcine models. This marks a substantial advancement in tailoring the mechanical properties of hydrogels for stem cell-assisted tissue regeneration.